Pengaruh Model Pembelajaran Kooperatif Tipe Number Heads Together (NHT) Terhadap Hasil Belajar Sejarah - Eka Sari Handayani (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2016)
This research aims to determine the effect of cooperative learning model type Numbered Head Together (NHT) toward learning history outcomes at SMA Negeri 3 Kabupaten Tangerang. This research is quantitative approach with experimental method. From the result of statistical calculation, it can be concluded that there is a significant effect in cooperative learning model type Numbered Head Together (NHT) toward learning history outcomes which come out from tcount value 5,961 >ttable 2,00 with significant rate 0,05.